Primary medullary adenocarcinoma of the colon: Literature review and case series - Hein Maung; Oliver Gregory; Thomas De Hoog; Matthew Hutchinson; Dr. Pith Beh Soh; Matthew Marino; Tobias Evans; Adrian Yeoh; Richard C. Turner (Surgery in Practice and Science)
Aims: Medullary carcinoma of the colon is a rare subtype of adenocarcinoma, first described in 1999. Clinically known to have a favourable prognosis in comparison to poorly differentiated cancers, it is associated with deficient mismatch repair. This is an observational single center study of patients with medullary cancer, and comparison with the current literature. Methods: We performed a search of the pathological database at our institution for medullary adenocarcinomas between the years of 2016–2023 and reviewed their clinical information to collect all relevant data including patient history, hospital admissions. surgery and clinic visits. We then performed a literature search using Pubmed for search terms medullary cancer/carcinoma of the colon/colorectum. Results: 11 patients were found in our database, 34 studies in the literature, 19 retrospective cohort studies (3144 patients) and 13 case reports. 81.8% (vs. 73.22% in cohort studies) were female patients. 8/11 patients' tumours had lympho-vascular invasion with 2/11 perineural involvement. Immunohistochemistry demonstrated 11/11 patients’ tumours with MLH1 and PMS2 loss, and presence of MSH2 and MSH6. Cohort studies demonstrated 302/1897 (15.92%) tumours had perineural invasion with 1133/2151 (52.67%) demonstrating lympho-vascular invasion. MLH1 testing was available for 192 patients, with 93.75% having loss of MLH1. Conclusion: Our cohort of medullary cancer patients were similar to that in the literature, with regards to demographics, staging and tumour characteristics. A longer follow-up time is required for our cohort to analyze long term survival outcomes.